Neurologic Alterations Due to Respiratory Virus Infections - Bohmwald, Karen; Gálvez, Nicolás M. S.; Ríos, Mariana; Kalergis, Alexis M. (Frontiers in Cellular Neuroscience, 2018)
Central Nervous System (CNS) infections are one of the most critical problems in public health, as frequently patients exhibit neurologic sequelae. Usually, CNS pathologies are caused by known neurotropic viruses such as measles virus, herpes virus and human immunodeficiency virus, among others. However, nowadays respiratory viruses have placed themselves as relevant agents responsible for CNS pathologies. Among these neuropathological viruses are the human respiratory syncytial virus (hRSV), the influenza virus (IV), the coronavirus (CoV), and the human metapneumovirus (hMPV). These viral agents are leading causes of acute respiratory infections every year affecting mainly children under five years old and also the elderly. Up to date, several reports have described the association between respiratory viral infections with neurological symptoms. The most frequent clinical manifestations described in these patients are febrile or febrile seizures, status epilepticus, encephalopathies, and encephalitis. All these viruses have been found in cerebrospinal fluid (CSF), which suggests that all these pathogens, once in the lungs, can spread throughout the body and eventually reach the CNS. The current knowledge about the mechanisms and routes used by these neuroinvasive viruses remains scarce. In this review, we describe the most recent findings associated to neurologic complications, along with data about the possible invasion routes of these viruses in humans and their various effects on the CNS, as studied in animal models.